Epistemological Integration in the Ma'had Aly Curriculum: An Analysis of the Bayānī-Burhānī -’Irfānī Trilogy in the Fiqh wa Ushuluhu Program of Ma'had Aly At-Tarmasi Pacitan - Muhammad Amruddin Latif (Global Education Journal, 2025)
This study operationalizes the trilogy of al-Jabiri epistemology (bayānī–burhānī –'irfānī) to map the epistemological orientation of the Ma'had Aly curriculum through the al-Jabiri Epistemology Coding Framework v1.0 (27 indicators; three dimensions: Sources of Authority, Methods of Acquisition, and Validation of Knowledge Claims). The framework is applied to the curriculum of Ma'had Aly At-Tarmasi (Pacitan) of the Takhassus Fiqh wa Ushuluhu program through the analysis of curriculum documents, syllabus, and book reference lists, with an independent intensity rating scoring system (0–3) that allows the capture of simultaneous multi-epistemological manifestations. The results showed strong epistemological integration: high bayānī (M = 2.58; SD = 0.87), high bursity (M = 2.52; SD = 0.82), and moderate irrationality (M = 1.88; SD = 1.01); in the Takhassus category (69 credits) there was a simultaneous high intensity in bayānī (M = 3.00) and burhānī (M = 2.78), indicating organic synthesis rather than a zero-sum trade-off. Bayānī is manifested in authoritative turāts (100% classical writings), explicit sanad, and qiyās; burhānī in systematic istinbāṭ methodology, causal analysis ('illat, maqāṣid), and baḥts al-masā'il; whereas 'irfānī is primarily on social transformation (M = 2.67) and exemplary (M = 2.50), rather than intuitive-mysticism (M = 0.67). These findings challenge al-Jabiri's thesis of "bayānī hegemony" in the context of contemporary Islamic education and offer a replicable methodological contribution to a cross-Ma'had Aly comparative analysis.